Attitudes of Teaching stuff and administrators at Saudi electronic university towards electronic tests and the extent to which they apply universal design standards UDL, difficulties and suggestions - Dardeer, Meaad Mohammed; Al-Ahmari, Nayfa Abdullah; Al-Harbi, Hawazen (Journal of Curriculum and Teaching Methodology, 2024)
The aim of this research is to find out the attitudes of teaching stuff and administrators at Saudi electronic university towards electronic tests and the extent to which they apply UDL universal design standards, difficulties, and proposals. And the researchers use analytical descriptive approach, It was distributed to a purposive sample of the university’s faculty and administrative staff, whose number reached (84) in all branches in the Kingdom of Saudi Arabia The results of the study revealed that the faculty members’ attitudes toward implementing electronic tests at the university and their preference for them compared to paper tests obtained an overall average of (4.11 out of 5); With a (large) degree, the difficulties and challenges faced by faculty members while applying electronic tests received an overall average of (3.74 out of 5); With a (large) degree, finally the faculty’s proposals included the importance of providing alternative computers for students and the importance of showing immediate results to the student, and obtained an overall average of (4.64 out of 5); With a (large) degree, Based on the results, the two researchers recommended the necessity of providing training courses for faculty members and students regarding solving hardware problems and dealing with educational platforms, the necessity of taking the opinion of faculty members in the process of developing the educational platform, adhering to comprehensive design standards as a reference, the necessity of providing alternatives for students, and paying attention to communications infrastructure, in addition to Proposals for conducting complementary studies on the subject.
Keywords: Faculty members’ attitude; Universal Design Standards (UDL); Evaluation; Electronic Tests; Saudi electronic university